Development of computer-based virtual patients for training and assessment of self-medication consultation skills in pharmacy students - Guerreiro, M. P. (2015)
Poster presented at the ESCP International Workshop 2015 in Collaboration with SFPC. Nice, France, 22-13 June 2015.